2011
DOI: 10.1111/j.1468-1331.2011.03612.x
|View full text |Cite
|
Sign up to set email alerts
|

The cost of headache disorders in Europe: the Eurolight project

Abstract: Headache disorders are prominent health-related drivers of immense economic losses for the EU. This has immediate implications for healthcare policy. Health care for headache can be both improved and cost saving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
523
6
34

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 605 publications
(581 citation statements)
references
References 26 publications
18
523
6
34
Order By: Relevance
“…In Europe, this cost is estimated at €1222 [39,40]. Migraine burden is bound to increase by more than 10% DALYs within the next decade [41].…”
Section: Therapeutic Aspectsmentioning
confidence: 99%
“…In Europe, this cost is estimated at €1222 [39,40]. Migraine burden is bound to increase by more than 10% DALYs within the next decade [41].…”
Section: Therapeutic Aspectsmentioning
confidence: 99%
“…Jellemzően a 40-50 év közötti korosztályban a leggyakoribb [10]. Részben ezzel, részben gyakoriságával magyaráz-ható, hogy az FTTF társadalmi szinten a legköltségesebb neurológiai betegségek közé tartozik [11]. A költségek túlnyomó része úgynevezett indirekt költség, amely a gyakori fejfájások miatt kieső vagy csökkent produktivitású munkából adódik.…”
unclassified
“…Chronic migraine associated to medication overuse (CM-MO) is an unfavourable outcome of migraine course, which seems to be mediated by lifestyle, life events, comorbid conditions, genetic terrain and medication overuse [1,2], and which determines a relevant burden, in particular in terms of increased disease cost [3]. A recent review showed that patients with a chronic form of headache report a remarkable impact on functioning, with high disability and reduction in work and non-work activities [4].…”
Section: Introductionmentioning
confidence: 99%